Timing of episiotomy and outcome of a non-instrumental vaginal delivery - Rusavy, Zdenek; Karbanova, Jaroslava; Kalis, Vladimir (Acta obstetricia et gynecologica Scandinavica, 2016)
INTRODUCTION: The aim of this study was to compare to compare immediate delivery outcome as well as healing, pain, anal incontinence and sexuality in a short-term and a long-term follow up after episiotomy performed before or at crowning in nulliparous women. MATERIAL AND METHODS: This cohort study is a comparison of prospectively collected data evaluating the importance of the timing of episiotomy. Patients with episiotomy performed before crowning (n = 86) and at crowning (n = 404) were compared. Obstetric anal sphincter injuries rate, additional perineal or vaginal trauma, neonatal outcome, episiotomy length, 2nd stage of labor duration, blood loss, infection, hematoma, dehiscence, need for resuturing, pain, painful defecation, resumption of sexual intercourse, dyspareunia, anal incontinence and constipation were assessed immediately after delivery or from responses to questionnaires 24 and 72 h, 10 days, 3 and 6 months postpartum. RESULTS: The groups did not differ in age, body mass index, birthweight, occipito-posterior presentation, shoulder dystocia, or episiotomy type. Significant differences between before crowning and at crowning groups were observed in additional vaginal trauma [26 (30.2%) vs. 66 (16.3%), respectively, p < 0.001], mean episiotomy length (42 mm vs. 36 mm, p < 0.001), and mean estimated blood loss (367 mL vs. 344 mL, p < 0.001). Difference in obstetric anal sphincter injuries rate did not reach statistical significance [0 (0.0%) vs. 7 (1.7%), p = 0.61]. The groups did not differ in additional perineal trauma, pain (Visual Analogue Scale, Verbal Rating Scale and Activities of Daily Living scales), healing complications, sexual functions or anal incontinence in short-term or long-term follow up. CONCLUSIONS: Our results suggest that episiotomy performed at crowning is not associated with worse anatomical or functional delivery outcome, and support a restrictive approach to episiotomy. The effect of episiotomy timing on pelvic organ prolapse development remains to be determined.
Keywords: hojení ran; Surveys and Questionnaires; childbirth; timing; Pain Measurement; výsledek těhotenství; Episiotomy; Humans; Pregnancy; Sexual Behavior; delivery outcome; Female; dospělí; Pregnancy Outcome; lidé; Fecal Incontinence; fekální inkontinence; Wound Healing; časové faktory; crowning; průzkumy a dotazníky; Adult; Postoperative Complications; pooperační komplikace; epiziotomie; ženské pohlaví; těhotenství; prospektivní studie; Time Factors; sexuální chování; měření bolesti; Prospective Studies